Automatic display of fetal brain planes and automatic measurements of fetal brain parameters by transabdominal three‐dimensional ultrasound. Issue 2 (18th July 2019) - Meng, Lu; Zhao, Dan; Yang, Zeyu; Wang, Bing
Abstract: Objective: The primary purpose of this study was to evaluate the effectiveness of a three‐dimensional (3D) software tool (smart planes) for displaying fetal brain planes, and the secondary purpose was to evaluate its accuracy in performing automatic measurements. Material and methods: This prospective study included singleton fetuses with a gestational age (GA) greater than 18 weeks. Transabdominal two‐dimensional ultrasound (2DUS) and 3D smart planes images were respectively used to obtain the basic planes of the fetal brain, with five parameters measured. The images, by either two‐dimensional (2D) manual or 3D automatic operation, were reviewed by two experienced sonographers. The agreements between two measurements were analyzed. Results: A total of 226 cases were included. The rates of successful detection by automatic display were as high as 80%. There was substantial agreement between the measurements of the biparietal diameter, head circumference and transcerebellar diameter, but poor agreement between the measurements of cisterna magna and lateral ventricle width. Conclusions: Smart Planes might be valuable for the rapid evaluation of fetal brain, because it simplifies the evaluation process. However, the technology requires improvement. In addition, this technology cannot replace the conventional manual US scans; it can only be used as an additional approach.